Micronutrient Fertiliser Reinforcement by Fulvate–Lignosulfonate Coating Improves Physiological Responses in Tomato - Ricardo Gil-Ortiz; Miguel Ángel Naranjo; Sergio Atares; Oscar Vicente; Raphaël Morillon (Agronomy, 2023)
Micronutrients are essential to plants, and enhancing their availability is one of the agronomic challenges to improving crop quality and yield. This study, under controlled greenhouse conditions, compares tomato plants’ responses to two different micronutrient EDTA-chelated formulations, one of them including a newly developed fulvate–lignosulfonate coating. Growth, yield, and several physiological parameters, including photosynthetic gas exchange, water-use efficiency, leaf nutrient content, leaf greenness and the effective quantum yield of photosystem II, were measured to compare their efficiency. The results showed that the new coated formulation significantly improved growth and most of the determined physiological parameters. At the end of the experiment, higher foliar levels of Fe (2.4-fold) and Mn (2.9-fold) were measured, revealing increased availability of lignofulfonate-complexed micronutrients compared to the traditional fertiliser. Moreover, the photosynthesis rate and stomatal conductance were 9- and 20-fold higher, respectively, than when using the standard fertiliser. In conclusion, the new coated fulvate–lignosulfonated fertiliser provided a more suitable source of micronutrients for tomato plant fertilisation, allowing for higher yields, which correlated with a generally improved physiological response.